Інноваційний підхід до формування розкладу польотів аероклубу за допомогою системи штучного інтелекту - Полозов, М. О. (ХНУРЕ, 2024)
This work defines the problem of formation of the flight schedule of the aero club and its methods. The algorithm for the introduction of innovative technologies in the aviation sector is presented. Methods of increasing the efficiency of artificial intelligence in the aero club are described. The process of training potential specialists to the aeroclub schedule formation system is described. The way to optimize the use of enterprise resources for the efficiency of the artificial intelligence system is described.
Keywords: формування розкладу; аероклуб; штучний інтелект; AI